Bright objects : a novel - Todd, Ruby (Simon & Schuster, 2024)
"A young widow grapples with the arrival of a once-in-a-lifetime comet and its tumultuous consequences, in a debut novel that blends mystery, astronomy, and romance, perfect for fans of Emma Cline's The Girls and Ottessa Moshfegh's Death in Her Hands"--